Explore the application of folk arts in wall painting art/ Qiu Chen ... [et al.] - Qiu, Chen; Ismail, Issarezal; Ramli, Ishak; Weiqin, Pan; Hadi, Hamidi (Universiti Teknologi MARA, Perak, 2024)
This study aims to analyse the inheritance of folk arts in the wall painting art as an example, and to propose the main measure for the application of folk arts in the wall painting art, to allow our country's folk arts to continue the inheritance while enriching the wall painting art form, and to encourage the integrated development of both. Folk arts refers to the art that is inherited and developed among the public. The purpose of folk arts creation is to beautify the environment and enrich the popular culture. Folk arts includes the traditional art forms of various ethnic groups in China and is the embodiment of various art forms. Folk and traditional arts are rooted in and reflective of the cultural life of a community. They encompass the body of expressive culture associated with the fields of folklore and cultural heritage. Tangible folk arts include historic objects which are crafted and used within a traditional community. It applies a qualitative, because of its flexibility in recording observations of elements of folk arts in wall painting. To this day, wall painting still has a large market in Chinese society, and folk arts has gradually developed into the most popular element. Overall, this study will provide an invaluable source of information about folk arts and wall painting. It will benefit wall painting designers, artists, researchers, art students, and scholars interested in studying this theme and traditional elements.